Isogenic induced pluripotent stem cell line ICGi036-A-1 from a patient with familial hypercholesterolaemia, derived by correcting a pathogenic variant of the gene LDLR c.530C>T - A. S. Zueva; A. I. Shevchenko; S. P. Medvedev; E. A. Elisaphenko; A. A. Sleptcov; M. S. Nazarenko; N. A. Tmoyan; S. M. Zakian; I. S. Zakharova (Вавиловский журнал генетики и селекции, 2025)
Familial hypercholesterolaemia is a common monogenic disorder characterized by high plasma cholesterol levels leading to chronic cardiovascular disease with high risk and often early manifestation due to atherosclerotic lesions of the blood vessels. The atherosclerotic lesions in familial hypercholesterolaemia are mainly caused by pathogenic variants of the low-density lipoprotein receptor (LDLR) gene, which plays an important role in cholesterol metabolism. Normally, cholesterol-laden low-density lipoproteins bind to the LDLR receptor on the surface of liver cells to be removed from the bloodstream by internalisation with hepatocytes. In familial hypercholesterolaemia, the function of the receptor is impaired and the uptake of low-density lipoproteins is significantly reduced. As a result, cholesterol accumulates in the subendothelial space on the inner wall of blood vessels, triggering atherogenesis, the formation of atherosclerotic plaques. At present, there are no effective and universal approaches to the diagnosis and treatment of familial hypercholesterolaemia. A relevant approach to study the molecular genetic mechanisms of the disease and to obtain systems for screening chemical compounds as potential drugs is the generation of cellular models based on patient-specific induced pluripotent stem cells. The aim of our work was to derive an isogenic genetically modified induced pluripotent stem cell line by correcting the pathogenic allelic variant c.530C of the LDLR gene in the original iPSC previously obtained from a compound heterozygote patient with familial hypercholesterolaemia. The resulting isogenic iPSC line differs from the original by only one corrected nucleotide substitution, allowing us to study the direct effect of this pathogenic genetic variant on physiological changes in relevant differentiated cells. CRISPR/Cas-mediated base editing was used to correct the single nucleotide substitution. The resulting genetically modified iPSC line has pluripotency traits, a normal karyotype, a set of short tandem repeats identical to that in the original line and can be used to obtain differentiated derivatives necessary for the elaboration of relevant cell models.